Study on Liquefaction Resistance of Pile Group by Shaking Table Test - Cong Zhang; Zhongju Feng; Yunhui Guan; Huiyun Chen; Fuchun Wang; Boxi Xu (Advances in Civil Engineering)
This study investigated the antiliquefaction property of the pile group. It is shown in the pore pressure ratio, pile acceleration, and bending moment response of saturated silt fine sand. The response law of pile acceleration and bending moment during liquefaction development is proved. The results show that liquefaction occurs in single piles, four piles, and six piles under the action of 0.35 g seismic wave. But the time of liquefaction is different. There is an obvious difference in the response of pile acceleration and bending moment during liquefaction. Liquefaction in the saturated silt fine sand develops from shallow to deep. The complete liquefaction of six piles takes the longest time, while the single pile takes the shortest time, and the average delay was 8.82 s. With the increase of the number of piles, there are some differences in pile acceleration, magnification factor, and pile bending moment, which are mainly reflected in time. The peak acceleration appearance of six piles was 3.08 s later than that of the single pile on average. The maximum bending moment appearance of six piles was 1.96 s later than that of the single pile on average. The acceleration and bending moment of the pile begins to attenuate when the pore pressure ratio increases. It shows that the saturated silt fine sand has softening and damping effect before liquefaction. In summary, the antiliquefaction performance of the pile group is better than that of a single pile. In the seismic design of pile foundation in liquefied soil, the antiliquefaction performance of the pile group is better.